2012
DOI: 10.1161/strokeaha.112.650838
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atrial Fibrillation on Outcome in Thrombolyzed Patients With Stroke

Abstract: Background and Purpose-Atrial fibrillation has been considered a risk factor for poor outcome from acute stroke and may influence response to thrombolysis, although supporting data are limited due to potential confounding with age and stroke severity. Method-We assessed the association of atrial fibrillation and thrombolysis exposure with the modified Rankin Scale score distribution at 90 days among patients registered in a trials archive. We used an age and baseline National Institutes of Health Stroke Scale-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…There was no significant difference in ICH (asymptomatic or symptomatic) between AF and non-AF patients among tPA or controls. 31 In contrast to the VISTA results, we found a trend for a favorable outcome after tPA among AF patients, but not reaching significance, likely explained by the smaller tPA sample in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in ICH (asymptomatic or symptomatic) between AF and non-AF patients among tPA or controls. 31 In contrast to the VISTA results, we found a trend for a favorable outcome after tPA among AF patients, but not reaching significance, likely explained by the smaller tPA sample in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…30 In the VISTA Collaboration, among 3027 patients receiving thrombolysis, 1631 (53.9%) had a history of AF. 31 The authors found a similar magnitude of benefit with tPA compared with placebo for patients with AF (OR, 1.44; 95% CI, 1.12-1.73) and without AF (OR, 1.53; 95% CI, 1.39-1.69). Similar to our findings (Figure 1), non-AF patients receiving tPA had a better favorable outcome (49.3% versus 33%; OR, 0.81; 95% CI, 0.66-1.00) if the mRS is categorized as 0 to 2 versus 3 to 6.…”
Section: Discussionmentioning
confidence: 89%
“…1, 5 However we found no evidence for this, in keeping with larger studies demonstrating no differential effect of thrombolysis on cardioembolic compared to non-cardioembolic strokes. 19,20 Similar to our findings, a recent study found no difference in HU ratio or early recovery depending on whether the aetiology of thrombus was thought to be cardioembolic or atherothrombotic. 9 The significant trend towards reduced parenchymal haemorrhage we observed in patients with HMCAS disappearance is likely due to the smaller ischaemic volume, represented by higher ASPECTS scores and reduced stroke severity.…”
Section: Discussionsupporting
confidence: 90%
“…Nine studies 8,10,1821,2325 reported all-cause mortality in hospital 8,20,21,23 and at the end of the follow-up period 10,18,19,24,25 for the IS patients in each group (Figure 2). Pooled data using the random-effect model showed that patients with acute IS and AF were more likely to die following intravenous thrombolysis in the short term compared to those without AF (OR, 1.88; 95% CI: 1.43–2.48, P  < 0.001, I 2  = 70%).…”
Section: Resultsmentioning
confidence: 99%